ANALYSIS OF THE HARMONIC AND POWER FACTOR EFFECT ON THE KWH METER MEASUREMENTS - Budianto Handoyosuryo, Arief
PT PLN (Persero) is an electrical energy company which as a utility serves customers with various types of loads. As technology develops, customer loads, especially industrial customers, are increasingly dominated by non-linear loads such as Variable Frequency Drive (VFD). The switching mechanism for non-linear loads will cut the sinusoidal waveform of voltage and current into an impure sinusoidal waveform. The process of changing the shape of a sinusoidal wave is known as harmonic distortion. Technological developments in the electric power system, especially for industrial customers, have also resulted in low power factor values for some industrial customers.. The accuracy of measuring electrical energy is very important to create business fairness between utility companies and customers, therefore this research presents an investigation of the impact of harmonics and power factor on kWh meters used by PT PLN (Persero) on industrial customers. The research results show that harmonics have an influence on the measuring power and also the accuracy (deviation) of the kWh meter, while the power factor has no effect on the accuracy of the kWh meter. The test is carried out by supplying a load containing harmonic sources of orders 3, 5, and 7 alternately with values referring to IEC 62052-11 2020, while testing the influence of power factor uses varying power factor values with intervals of 0,1 such as power factor conditions in PT PLN (Persero) industrial customers . The Testing of harmonic effect on measured power uses the empirical formula that reference to IEEE Std 1459-2010. We found that the active power of the 3rd order and 5th order harmonics has a reverse direction (minus) compared to the fundamental active power, while the 7th order harmonic distortion causes an increase in the active power. The research results show that the formula used by the kWh meter to calculate reactive power due to the influence of harmonics is not in accordance with IEEE Std 1459-2010. The results of the kWh meter accuracy test show that harmonics cause the kWh meter measurement deviation to exceed the limit in the accuracy class where 7th order harmonics cause an error of +0.535%, 3rd order causes an error of -0.985% and 5th order causes an error of -0.990. The results of kWh meter accuracy testing also show that the power factor does not affect accuracy of the kWh meter.